1997
DOI: 10.1088/0022-3727/30/20/015
|View full text |Cite
|
Sign up to set email alerts
|

A departure from local thermodynamic equilibrium within a freely burning arc and asymmetrical Thomson electron features

Abstract: Spectrally resolved measurements of Thomson scattering were made in a freely burning arc in argon at a pressure of 1 atm. The radial and axial profiles in electron temperature and number density exhibited extensive regions of departure from local thermodynamic equilibrium, so confirming the findings of Snyder et al in E 48 4124 - 7, 1993. Electron temperatures at least 4000 K above those of the gas were found. Asymmetry in the Thomson electron feature was found and shown to depend on which segment of the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
7
31
1
Order By: Relevance
“…From these results, obviously, he showed the deviation from LTE in the arc core. Furthermore, his measurements implied [20] also carried out the similar measurements to Snyder [19]. He showed that the peak electron temperature was 20,400 K at 2 mm below the cathode tip under the similar conditions in the free-burning argon arc, and then confirmed the findings of Snyder [19] by comparison with 16,000 K which Murphy [21] showed as the heavy particle temperature.…”
Section: Introductionsupporting
confidence: 52%
“…From these results, obviously, he showed the deviation from LTE in the arc core. Furthermore, his measurements implied [20] also carried out the similar measurements to Snyder [19]. He showed that the peak electron temperature was 20,400 K at 2 mm below the cathode tip under the similar conditions in the free-burning argon arc, and then confirmed the findings of Snyder [19] by comparison with 16,000 K which Murphy [21] showed as the heavy particle temperature.…”
Section: Introductionsupporting
confidence: 52%
“…[1][2][3] Thus, understanding the relation among the temperatures of the arc plasma, the distributions of current and heat input on the anode, and the results is quite important for the materials processing by the free-burning arcs. However, experimental and theoretical investigations of the temperature of arc plasma, [3][4][5][6][7][8][9] the distributions of current and heat input, 10,11) and results, for example, the weld penetration [12][13][14][15][16] were separately conducted and the relation among them has not been made clear. For example, Nestor 10) measured the distributions of current and heat input on the anode of freeburning arc by using the water-cooled copper anode which consists of two separate blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of Thomson scattering is explicated by many literatures [7][8][9][10][11]13]. Figure 2 shows the comparison between electron temperature for the pure helium arc with the water-cooled copper anode (left side) and that for the helium arc during welding (right side) under the same condition of 150 A in arc current and 5 mm in arc length.…”
Section: Temperature Distributions 21 Experimental Set Upmentioning
confidence: 99%
“…They showed that electron temperature was different from heavy particle temperature. Bentley [9] and Murphy [10] also showed deviation from LTE in GTA plasma. Furthermore, Tanaka and Ushio [11] showed non-LTE state in argon GTA and insisted that the non-LTE state in GTA was caused due to the cathode jet induced by arc constriction at the tungsten electrode.…”
Section: Introductionmentioning
confidence: 95%